"Among the civilized" : a consideration of family, power, morality and technique in the novels of Ivy Compton-Burnett - Novis, Carol (Department of English Language and Literature, 2016)
The purpose of this thesis is to attempt to penetrate beyond these mystifying eccentricities of style to Ivy Compton-Burnett's world view, in order to show that, rather than being limited and inflexible, they are limited only to the extent that they establish the bounds within which a rich and varied world exists. If these novels can be said to be "about" anything, they are about the difficulties of living as a civilized being in a savage world, and about the depths of human motives and reactions. To illustrate this, my approach is thematic, rather than chronological.